Notable Carrier Risks for Individuals Having Two Copies of SMN1 in Spinal Muscular Atrophy Families with 2‐copy Alleles: Estimation Based on Chinese Meta‐analysis Data. Issue 1 (16th July 2016) - Wei, Xianda; Tan, Hu; Yang, Pu; Zhang, Rui; Tan, Bo; Zhang, Yue; Mei, Libin; Liang, Desheng; Wu, Lingqian
Abstract: Spinal muscular atrophy is an autosomal recessive neuromuscular disease mainly caused by homozygous deletion of SMN1 . The 2‐copy SMN1 allele may present in the families of SMA patients with homozygous deletion of SMN1, one of whose parents has two SMN1 copies. In such families, individuals having two SMN1 copies still have a chance to be "2 + 0" carriers. In this study, the risks for the parents, fetuses and other siblings having two SMN1 copies to be "2 + 0" carriers were estimated based on Chinese meta‐analysis data and turned out to be rather striking. Our findings would help to optimize genetic counseling regarding spinal muscular atrophy.